Population structure and breeding period of Pachycheles monilifer (Dana) (Anomura, Porcellanidae) inhabiting sabellariid sand reefs from the littoral coast of São Paulo State, Brazil - Fransozo, Adilson [UNESP] (2001)
The purpose of the present study is to examine the population structure and the breeding period of Pachycheles monilifer (Dana, 1852) inhabiting sabellariid worm reefs in the littoral of São Paulo State coast. The specimens were obtained at 2-month intervals from September/94 to July/95. The study sites were located at the rocky shores of Tenorio and Paranapuã Beaches. Individuals sampled showed a total averaged 4.4 ± 1.4 mm carapace length. Ovigerous females were more frequent in September. Despite clear differences regarding the arrangement of these sabellariid colonies, they are extremely important to the establishment and maintenance of P. monilifer.